Fusarium and Alternaria mycotoxins present in Canadian wheat and durum harvest samples. Issue 3 (3rd July 2019) - Tittlemier, Sheryl A.; Blagden, Richard; Chan, Jason; Gaba, Don; Mckendry, Twylla; Pleskach, Kerri; Roscoe, Mike
Abstract: The objectives of this work were to investigate the presence of a variety of mycotoxins in Canadian wheat and durum and to characterize the relationship between concentrations of the Fusarium- produced deoxynivalenol (DON) and the presence of visible Fusarium damage. There is a lack of reported mycotoxin surveillance data for Canadian wheat and durum; this work addresses this information gap. Wheat and durum harvest samples from the 2010, 2011 and 2013–2016 growing seasons were analysed for mycotoxins produced by a variety of fungal species, including Fusarium graminearum and Alternaria alternata . The Alternaria -produced tentoxin was observed the most frequently; it was present in 90% of the samples analysed at concentrations up to 0.063 mg kg −1 . Fusarium -produced DON and enniatins B and B1 were present in over 70% of samples analysed. The plant transformation product DON-3-glucoside was quantified in up to 30% of samples. There was variability in the presence of the various mycotoxins amongst years. In particular, for DON, the variability reflected the level of visible Fusarium damage noted in grain samples. The geographic source of samples also influenced DON concentrations, which decreased from eastern to western growing regions on the Prairies. Concentrations of DON varied from 0.066 to 0.895 mg kg −1 in south central Manitoba and <0.03 to 0.053 mg kg −1 in central Alberta. DON concentrations were significantly correlated (P < 0.001) with visible Fusarium damage in Canada Western Red Spring wheat for all four years investigated. For Canada Eastern Soft Red Winter wheat and Canada Western Amber Durum, there were significant correlations (P < 0.001) in three of the four years investigated for each grain class. The years with no significant correlation between DON and Fusarium damage occurred when the presence of Fusarium species other than the DON-producing F. graminearum were predominant. This work provides a picture of the presence, and absence, of a number of mycotoxins in Canadian wheat and durum.